2011
DOI: 10.1097/tp.0b013e3182079474
|View full text |Cite
|
Sign up to set email alerts
|

Subcapsular Fetal Pig Pancreas Fragment Transplantation Provides Normal Blood Glucose Control in a Preclinical Model of Diabetes

Abstract: This study confirms that fetal pig islet tissue has the potential to mature and function normally in a neovascularised site, hence, avoiding the innate immune destruction that occurs when islet tissue is exposed directly to the circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…Portal vein, liver (Pepper et al, 2013;Carlsson et al, 2001), spleen (Gray, 1990), omentum, pancreas, muscle, gastric sub mucosa, subcutaneous, genitourinary tract, anterior eye chamber, thymus and testis are the suggested sites for animal islet transplantation (Cantarelli and Piemonti, 2011;Rajab, 2010). Renal sub capsular space can provide a better condition for transplanted islet cells (Mellgren et al, 1986;Si et al, 2001;Hawthorne et al, 2011) and it is the most widely used site in rodents (Pepper et al, 2013). Also, in human it was reported that kidney, liver, muscle, and omentum are respectively the best sites for islet transplantation (Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Portal vein, liver (Pepper et al, 2013;Carlsson et al, 2001), spleen (Gray, 1990), omentum, pancreas, muscle, gastric sub mucosa, subcutaneous, genitourinary tract, anterior eye chamber, thymus and testis are the suggested sites for animal islet transplantation (Cantarelli and Piemonti, 2011;Rajab, 2010). Renal sub capsular space can provide a better condition for transplanted islet cells (Mellgren et al, 1986;Si et al, 2001;Hawthorne et al, 2011) and it is the most widely used site in rodents (Pepper et al, 2013). Also, in human it was reported that kidney, liver, muscle, and omentum are respectively the best sites for islet transplantation (Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Westran pigs were used as donor and recipients [7]; these pigs have been shown previously to be significantly inbred and as such do not require immunosuppression [10]. All procedures were approved by the Sydney West Area Health Service Animal Ethics Committee and conducted in compliance with the guidelines of the National Health and Medical Research Council of Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Although adult pig islets have been shown to survive in such circumstances when autologous tissue is used, adult pig islets are technically difficult to prepare and donor pigs must be housed in clean conditions for very long periods which creates significant expenses and substantial logistical and regulatory problems [6]. In a previous study, we have shown that foetal pig pancreas fragments (FPPF) could survive, develop and function normally in a subcapsular space that would make them an ideal source of islet tissue for islet‐renal composite grafts [7]. Direct comparison of the development of FPPF tissue transplanted into various sites had also previously been undertaken to provide the control comparative data for the direct implantation of similar amounts of FPPF into different organs.…”
Section: Introductionmentioning
confidence: 99%
“…5 In contrast, our focus now lays on the immature islets such as the neonatal islet cell clusters (NICCs) which are able to be performed at an early age not requiring costly growth to adult pigs, are readily easy to isolate, show superior revascularization, and expand after transplantation. 6 Irrespective of donor age, however, pig islet xenografts provoke a strong immune response in non-human primates humans 7 . While islets can be protected to some degree from this response by encapsulation in a protective layer or device, the results of clinical trials of encapsulated WT adult pig islets have been disappointing.…”
Section: Advan Cing Pi G Is Le Ts For Xenotr Ans Pl Antationmentioning
confidence: 99%